Boundary EEG Asymmetry Is Associated to Linguistic Competence in Vascular Cognitive Impairments - Shibata, Takashi; Musha, Toshimitu; Kosugi, Yukio; Kubo, Michiya; Horie, Yukio; Tanaka, Mieko; Matsuzaki, Haruyasu; Kobayashi, Yohei; Kuroda, Satoshi (Frontiers in Human Neuroscience, 2018)
Background and Purpose: We recently noted a gradual change in the boundary electroencephalography (EEG) oscillation of 7.8 Hz between theta (θ) and alpha (α) bands in response to increased atherosclerosis levels in the elderly. The aim of this study was to investigate the role of boundary EEG oscillations of θ-α bands on cognitive functions in vascular cognitive impairments (VCI) patients. Materials and Methods: We examined 55 patients with VCI in carotid stenosis, and underwent EEG in a resting state with closed eyes for 5 min. The asymmetry index (AI) along homologous channel pairs (e.g., F7-8) was assessed using neuronal activity topography (NAT). AI referring to 10 frequency components ranging from 4 to 20 Hz and neuropsychological assessments including linguistic competence were analyzed. Results: The main findings was that the language score had a positive association with AI in 7.8 Hz at F7-8 and a negative association with AI in 6.3 Hz at C3-4 and 14.1 Hz at F3-4. Conclusion: EEG asymmetry in a boundary range might have a special role in linguistic competence, suggesting the application of neural oscillation on the cognitive function evaluation and neurorehabilition induced by a frequency-specific transcranial alternating current stimulation.